Restenosis of a Polytetrafluoroethylene-Covered Stent Visualized by Coronary Angioscopy and Optical Coherence Tomography: A Case Report - Araki, Makoto; Hikita, Hiroyuki; Sudo, Yuta; Hishikari, Keiichi; Takahashi, Atsushi (International Journal of Angiology, 2020)
An expandable polytetrafluoroethylene (PTFE)-covered stent graft is beneficial for the treatment of coronary perforations. However, several reports have shown that restenosis and thrombotic occlusion occasionally occur in the stented segment after PTFE-covered stent implantation. A restenosis case after treatment with PTFE-covered stent against saphenous vein graft (SVG) perforation has never been evaluated with optical coherence tomography (OCT) or coronary angioscopy (CAS). This case report presents a 75-year-old man treated with a PTFE-covered stent after he suffered from SVG perforation 6 months ago. He was found to have a focal restenosis of the distal edge of the PTFE-covered stent and underwent percutaneous coronary intervention. OCT showed focal restenosis with homogeneous neointima and exposed struts in the middle and proximal part of the PTFE-covered stent. CAS showed white neointima with a smooth surface at the restenosis site and a sharp border against proximal exposed struts with characteristic links. This case study showed, for the first time in vivo and in a human, the neointimal characteristics of restenosis and uncovered stent struts in a PTFE-covered stent which had been implanted 6 months before. The delayed endothelialization was sustained until 12 months after implantation.
Keywords: percutaneous coronary intervention; polytetrafluoroethylene-covered stent; case study; coronary angioscopy; optical coherence tomography; PCI; OCT